2019
DOI: 10.1038/s41598-019-45443-1
|View full text |Cite|
|
Sign up to set email alerts
|

Localization of RalB signaling at endomembrane compartments and its modulation by autophagy

Abstract: The monomeric GTPase RalB controls crucial physiological processes, including autophagy and invasion, but it still remains unclear how this multi-functionality is achieved. Previously, we reported that the RalGEF (Guanine nucleotide Exchange Factor) RGL2 binds and activates RalB to promote invasion. Here we show that RGL2, a major activator of RalB, is also required for autophagy. Using a novel automated image analysis method, Endomapper, we quantified the endogenous localization of the RGL2 activator and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Finally, to evaluate the impact of oncogenic Ras on autophagy topology in a genetically controlled cell model, we compared isogenic normal HEK-HT cells (human embryonic kidney cells, immortalized but not transformed) and transformed HEK-HT-H-RasV12 cells (tumorigenic, invasive, and metastatic, due to expression of constitutive active H-RasV12) [23,24]. Consistently with previous reports on Ras-mutated cancer cells [7][8][9], the transformation of HEK-HT cells by oncogenic H-RasV12 leads to increased autophagy [25].…”
Section: Introductionsupporting
confidence: 76%
“…Finally, to evaluate the impact of oncogenic Ras on autophagy topology in a genetically controlled cell model, we compared isogenic normal HEK-HT cells (human embryonic kidney cells, immortalized but not transformed) and transformed HEK-HT-H-RasV12 cells (tumorigenic, invasive, and metastatic, due to expression of constitutive active H-RasV12) [23,24]. Consistently with previous reports on Ras-mutated cancer cells [7][8][9], the transformation of HEK-HT cells by oncogenic H-RasV12 leads to increased autophagy [25].…”
Section: Introductionsupporting
confidence: 76%
“…Instead of total cellular RalA activity, it is possible that only a subset of RalA in specific cellular compartments is acting to promote LD accumulation. A recent study showed that RalB activity is increased specifically at autophagosomes upon starvation (Singh et al, 2019). Thus, we stably expressed either a GTPase-deficient RalA Q72L (GTP bound) or the dominant-negative RalA S28N mutant (GDP bound) in RalA KO MEFs (Figure S5C).…”
Section: Pld1 Is Required For Rala-dependent Starvationinduced Ld Accumulationmentioning
confidence: 99%
“…HeLa [8], HEK293T (CRL-3216; ATCC), and A549 (CCL-185; ATCC) cell lines were grown in DMEM (Gibco) supplemented with 10% FBS (Biosera), 1% penicillin/streptomycin (Gibco), and with 1% Lglutamine (Gibco). HeLa cells stably expressing the GFP-LC3-RFP-LC3DG autophagic flux probe (pMRX-IP-GFP-LC3-RFP-LC3DG, 84572; Addgene) as well as HEK-HT-iRFP-LC3 cells [49] were cultured in the appropriate medium supplemented with 1 lg/ml puromycin. Cells stably expressing APEX-STK38 (pWZL-APEX2-STK38; this work) were cultured in appropriate medium supplemented with 10 lg/ml blasticidin.…”
Section: Cell Culture and Drug Treatmentsmentioning
confidence: 99%
“…Cells stably expressing APEX-STK38 (pWZL-APEX2-STK38; this work) were cultured in appropriate medium supplemented with 10 lg/ml blasticidin. HeLa cells stably expressing the GFP-LC3-RFP-LC3DG autophagic flux probe (pMRX-IP-GFP-LC3-RFP-LC3DG, 84572; Addgene) as well as HEK-HT-iRFP-LC3 cells [49] were cultured in the appropriate medium supplemented with 1 lg/ml puromycin. HAP1 cell lines (C631; Horizon Discovery) were grown in IMDM (Gibco) supplemented with 10% FBS (Biosera), 1% penicillin/streptomycin (Gibco), and with 1% Lglutamine (Gibco).…”
Section: Cell Culture and Drug Treatmentsmentioning
confidence: 99%